The impact of shadow economy and government expenditure on tax ratios: Corruption’s role in ASEAN - Briliansyah, Lalu Hizby (Educoretax, 2025)
This study aims to analyze how shadow economy and government expenditure affect tax ratio and whether corruption perception index (CPI) can moderate these relationships. The shadow economy poses a significant challenge to tax revenue collection. Appropriate government expenditure is also expected to increase the tax base. However, the effectiveness of government expenditure is often undermined by corruption, which erodes public trust and compliance. This research was conducted using panel data regression. The samples used were countries in the ASEAN region between 2012 and 2020. The results show that shadow economy has a significant negative impact on tax ratio, while government expenditure has a positive effect. CPI significantly moderates these relationships, enhancing the negative impact of shadow economy and reducing the positive effect of government expenditure on tax ratio. The study concludes that reducing shadow economy and increasing government expenditure are crucial for improving tax ratio in ASEAN countries. However, the effectiveness of these measures depends on strong corruption control. Policymakers should prioritize anti-corruption efforts to enhance public trust and compliance, thereby optimizing tax revenue collection.